Native-speakerism revisited: Global Englishes, ELT and intercultural communication - Fan Fang (Universitas Katolik Indonesia Atma Jaya, 2018)
The English language functions as a global lingua franca, and as the number of non-native speakers of English surpasses the number of native speakers of English, the ideology of native-speakerism is challenged. Viewing from the paradigm of Global Englishes (GE), English is no longer the sole property of its native speakers. This paper first discusses and presents a general picture regarding standard language ideology and the ideology of native-speakerism, and links the notion to how such ideas would exert an influence on teacher recruitment and intercultural communication in English language teaching (ELT). This paper then employs narrative inquiry from Chinese ELT professionals who have education experience abroad to reveal how they negotiate their professional identities in relation to privilege and marginalization when working with native English speaking colleagues. This paper argues for the importance of moving beyond the idealized native speaker model from the GE paradigm to challenge the ideology of native-speakerism in various aspects of ELT, in particular, in expanding circle contexts.